1998
DOI: 10.1162/089892998562997
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of Involuntary Attention to Acoustic Novelty and Change

Abstract: Abstractn Behavioral and event-related brain potential (ERP) measures were used to elucidate the neural mechanisms of involuntary engagement of attention by novelty and change in the acoustic environment. The behavioral measures consisted of the reaction time (RT) and performance accuracy (hit rate) in a forcedchoice visual RT task where subjects were to discriminate between odd and even numbers. Each visual stimulus was preceded by an irrelevant auditory stimulus, which was randomly either a "standard" tone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

86
794
8
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 790 publications
(903 citation statements)
references
References 71 publications
(100 reference statements)
86
794
8
2
Order By: Relevance
“…The same pattern of results was found in a similar arrangement with auditory distracters and visual task-relevant stimuli (e.g. Escera et al, 1998;Escera, Yago, Alho, 2001;Yago, Corral, Escera, 2001). These ERPs are usually interpreted in terms of three distraction-related processing stages.…”
Section: Introductionsupporting
confidence: 69%
“…The same pattern of results was found in a similar arrangement with auditory distracters and visual task-relevant stimuli (e.g. Escera et al, 1998;Escera, Yago, Alho, 2001;Yago, Corral, Escera, 2001). These ERPs are usually interpreted in terms of three distraction-related processing stages.…”
Section: Introductionsupporting
confidence: 69%
“…P3a is generally assumed to reflect involuntary attention switching (Friedman et al, 2001;Polich, 2007), while RON is theorised to reflect the reorientation of attention to the original task (Schröger and Wolff, 1998a;Sussman et al, 2003). Similar results were found in auditory-visual paradigms in which targets were visual stimuli (e. g. odd or even numbers) and the distractors were sounds (Escera et al, 1998(Escera et al, , 2000(Escera et al, , 2001. Although the early studies using either auditory (Berti and Schröger, 2003;Schröger and Wolff, 1998a;Schröger and Wolff, 1998b) or auditory-visual (Escera et al, 1998(Escera et al, , 2000(Escera et al, , 2001 paradigms consistently found prolonged response times (RTs) and decreased accuracy, recent studies found abolished or even reversed behavioral effects (Li et al, 2013;Parmentier et al, 2010;SanMiguel, et al, 2010a;2010b;Wetzel et al, 2012).…”
Section: Introductionmentioning
confidence: 59%
“…Debener et al, 2005;Escera et al, 1998;Goldstein et al, 2002). ERP and fMRI studies suggest that a frontal attention mechanism governs neural responsivity to novelty (Daffner et al, 2000a(Daffner et al, , 2000b(Daffner et al, , 2000cSuwazono et al, 2000), thereby implying top-down control (Bledowski et al, 2004a;Dien et al, 2004;Kiehl et al, 2005;Opitz et al, 1999;Opitz, 2003).…”
Section: Neural Origins Of P3a and P3bmentioning
confidence: 99%